Designing a Modular-Approach of Multi-Microcontroller Based Educational Training System With IDE - Selvakumar, Raja Saravana Kumar; Nik Mohd Kamil, Nik Yusof; Kamarul Hawari, Ghazali (2009)

(untitled)
The advancement of microcontroller technology demands the need of everyone have grasp of this technology. In fact this technology is a compulsory course in any electrical or electronic field of engineering. This paper aims to describe development of a flexible microcontroller training system based on 8-bit microcontroller in Microchip, Motorola and Intel family. According to the latest survey, more than half of the total student in Faculty of Electrical & Electronics Engineering are having problem in understanding program structure and developing hardware. For this reason, the multi-microcontroller based development project will be designed to be as a learning tool for those who intend to learn microcontroller. With an extensive a development board, it could let the user to get start with their microcontroller application efficiently. The system provides a simple testing bed that offers various current applications such as Liquid Crystal Display (LCD), DC Motor, Keypad, DIP switches, sensors, multi-purpose displays and others that can be used extensively in experiments or projects. In addition, it is further boosted by the introduction of Integrated Development Environment (IDE) features in order to create user-friendly environment. By using this system, users are exposed to practical experience of the microcontroller and provide an easy path to learn this intelligent electronic device in short time. Without wasting too much time in preparing prototype circuit is one of the advantages by using a development board. In this respect, this multi-microcontroller Training System would be applicable for education and expose the electrical engineering students to the understanding fundamental of microcontroller in electronic design field.